Effect of magnetic field during the liquid – solid phase transition of some thermoplastic polymers (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Application of external fields on a polymer is common physical treatment for modifying the polymer properties. The field is applied on the final polymeric object or during synthesising or polymerization. In this work, the magnetic field from powerful permanent magnets was applied during the phase transition from liquid to solid phase, where the polymer chain interattraction forces are minimal. So, magnetic fields with less strength may perform valuable structural variations. It is found that magnetic field of 355 mT accelerated the spherulite growth in polyethylene glycol (PEG) films. High density polyethylene (HDPE) of zigzag chain, polypropylene (PP) of chains with side group and polystyrene (PS) as glassy polymer with ring, were magnetically treated with different field strength during their phase transition. Treated and untreated film samples were tested physically. IR- spectroscopy, X-ray diffraction, DTA, DSC and tensile stress – strain testing techniques were used in order to characterize, quantitatively, most types of the occurred variations if any. PS samples were casted by hot pressing and from dilute solution in magnetic field in order to detect the effect of solidification time on the size of the magnetic induced variations. Properties of treated HDPE showed little swinging about the untreatedvalue in the field strength up to 160 mT. PP properties showed serious variations in the same range of field strength. PS films casted from dilute solution showed stronger variations than the films casted by hot pressing of the melted PS. All data are presented in coloured graphs. Spherulites images are extracted from a video clip that is used in measuring the rate of PEG spherulite growth in magnetic fields